Območja razširjenosti in relativne gostote avtohtonih vrst parkljarjev v Sloveniji - Stergar, Matija (Gozdarski vestnik, 2009)
The knowledge of distribution and population densities of wild animals is important from both basic biological and management aspects. This is especially important for ungulates because of their ecosystem role (e.g. impacts on forest regeneration and forest dynamics, prey basis for large carnivores) and economic implications (damages in forestry and agriculture, hunting). The aim of this study was to determine and to present distribution and local densities of roe deer (Capreolus capreolus L.), red deer (Cervus elaphus L.), wild boar (Sus scrofa L.), and chamois (Rupicapra rupicapra L.) for whole Slovenia. We used data of recorded mortality (199 050 roe deer, 22 960 red deer, 31 777 wild boar, and 11 758 chamois) from the database of the "Central Slovenian register of game species and large carnivores" for the period 2004 - 2008, which are georeferenced with 1 km accuracy. We used fixed kernel method to present distribution maps for all four ungulate species with three ranks of their relative densities (95, 65, and 35 % of recorded dead animals). Distribution areas cover 79.2 %, 35.8 %, 46.0 %, and 21.9 % of territory of Slovenia for roe deer, red deer, wild boar, and chamois. We discuss the factors that affect or have affected distribution and densities of these species.
Keywords: parkljarji; prevalence; razširjenost; populacije; gostota; Slovenia; Slovenija